The relation between exercise and glaucoma in a South Korean population-based sample. - Shuai-Chun Lin; Sophia Y Wang; Louis R Pasquale; Kuldev Singh; Shan C Lin (PLoS ONE)
Purpose To investigate the association between exercise and glaucoma in a South Korean population-based sample. Design Population-based, cross-sectional study. Participants A total of 11,246 subjects, 40 years and older who underwent health care assessment as part of the 2008-2011 Korean National Health and Nutrition Examination Survey. Methods Variables regarding the duration (total minutes per week), frequency (days per week), and intensity of exercise (vigorous, moderate exercise and walking) as well as glaucoma prevalence were ascertained for 11,246 survey participants. Demographic, comorbidity, and health-related behavior information was obtained via interview. Multivariable logistic regression analyses were performed to determine the association between the exercise-related parameters and odds of a glaucoma diagnosis. Main outcome measure(s) Glaucoma defined by International Society for Geographical and Epidemiological Ophthalmology criteria. Results Overall, 336 (2.7%) subjects met diagnostic criteria for glaucomatous disease. After adjustment for potential confounding variables, subjects engaged in vigorous exercise 7 days per week had higher odds of having glaucoma compared with those exercising 3 days per week (Odds Ratio [OR] 3.33, 95% confidence interval [CI] 1.16-9.54). High intensity of exercise, as categorized by the guidelines of the American College of Sports Medicine (ACSM), was also associated with greater glaucoma prevalence compared with moderate intensity of exercise (OR 1.55, 95% CI 1.03-2.33). There was no association between other exercise parameters including frequency of moderate exercise, walking, muscle strength exercise, flexibility training, or total minutes of exercise per week, and the prevalence of glaucoma. In sub-analyses stratifying by gender, the association between frequency of vigorous exercise 7 days per week and glaucoma diagnosis remained significant in men (OR 6.05, 95% CI 1.67-21.94) but not in women (OR 0.96 95% CI: 0.23-3.97). A U-shaped association between exercise intensity and glaucoma prevalence was noted in men (OR 1.71, 95% CI 1.09-2.69 for low intensity versus moderate intensity; OR 2.19, 95% CI 1.25-3.85 for high intensity versus moderate intensity). Conclusion In a South Korean population sample, daily vigorous exercise was associated with higher glaucoma prevalence. In addition, the intensity of exercise was positively associated with glaucoma diagnosis in men but not women.